Multiple Papillomatosis of Breast and Patient's Choice of Treatment. (12th December 2010) - Debnath, Debasish; Al-Okati, Dhafir; Ismail, Wael
Abstract : Papillary lesions of breast represent a range of lesions. Intraductal papilloma and its association with nipple discharge are well known. However, multiple papillomatosis has quite distinct characteristics and decision making can be somewhat challenging. We report a case of multiple papillomatosis in association with ductal carcinoma in situ (DCIS). Patient opted for ipsilateral mastectomy and prophylactic mastectomy of contralateral breast. Her decision of having prophylactic mastectomy was vindicated by presence of incidental DCIS in the contralateral breast. To our knowledge, this is the first reported case of multiple papillomatosis with DCIS of breast, along with incidental synchronous papillomatosis of contralateral breast with DCIS. The case illustrates few distinct features of multiple papillomatosis of breast and exemplifies how a patient's choice is so paramount in decision making process. Patients should be fully informed of the treatment options of the condition, and their wishes should be fully taken into account while making the final decision.